Optimalisasi Link and Match Sebagai Upaya Relevansi SMK dengan Dunia Usaha dan Dunia Industri Berbasis Website pada SMK Yuppentek 1 Kota Tangerang - Eduard Hotman Purba; Haryanto Haryanto; Muhammad Zaidan; Mochamad Raihan Fadli (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Vocational education, particularly Vocational High Schools (SMK), plays a strategic role in preparing superior human resources who are competent in their fields and ready to enter the workforce. In this context, the government is encouraging the implementation of the Link and Match program as an effort to improve alignment and gaps between education and the needs of the workforce and the industrial world. However, the implementation of the Link and Match program in vocational high schools in the Tangerang area is currently still carried out conventionally. The communication process, recording collaborations, and managing Industrial Work Practice activities still rely on correspondence, manual messages, and face-to-face meetings. This condition results in data not being documented centrally, making it difficult for schools to obtain comprehensive information regarding program implementation. Therefore, an analysis of the current system is necessary to understand the current Link and Match implementation mechanism. Synchronizing the vocational curriculum with the needs of graduate users through the Link and Match program is expected to produce graduates with a professional attitude, achievement motivation, competence, and high competitiveness. The evaluation of this system is carried out using the Black Box Testing method.